Pengembangan Irigasi, Produksi Pangan, dan Implikasinya Terhadap Siklus Air - Sahid Susanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1992)
The cereal production especially rice has increased sharply in Indonesia. The irrigation development program implemented by the government has become an important rote in the production process. However, expansion of irrigated paddy lands significantly influence the hydrological regime in its basin. A set of basic indicator for assessing the hydrological implication of the development in a river basin was proposed.